The research of micro pattern transferring on metallic foil via micro-energy ultraviolet pulse laser shock. (November 2018) - Man, Jiaxiang; Yang, Haifeng; Liu, Hao; Liu, Kun; Song, Henan
Highlights: A micro-energy ultraviolet laser can fabricate micro pattern on aluminum foil. Overlap ratio and pulse laser energy impact on micro pattern depth obviously. Mold size has significant influence on transferred micro pattern depth. The local micro morphology of square micro pattern is distinct. Abstract: A micro-energy high frequency ultraviolet pulse laser was introduced for fabricating the micro pattern on pure aluminum foil by laser shock transferring. The copper mesh mold (mesh size: 400# and 1000#) and pure aluminum foil were used to investigate the effect of laser pulse energy and overlap ratio on micro pattern transferring. A FEM model was adopted to simulate the aluminum foil deformation and plastic strain in laser shock process. To investigate the micro forming mechanism of laser shock transferring, the micro morphology of significant area on processed micro pattern was observed by atomic force microscope (AFM). The experimental results revealed that the depth of transferred micro pattern increased with the increasing of single pulse energy and overlap ratio within certain range. The forming depth of aluminum foil imprinted from 400# mold was larger than that of 1000#, and more sensitive to pulse energy and overlap ratio. The aluminum foil on mold bars was smoother than that of on mold holes. The study demonstrated that the micro-energy ultraviolet pulse laser shock can realize the precise, controllable, fast and ultrahigh strain rate fabrication of surface microstructure.